2015
DOI: 10.1016/j.metabol.2015.08.011
|View full text |Cite
|
Sign up to set email alerts
|

BMI-related progression of atypical PKC-dependent aberrations in insulin signaling through IRS-1, Akt, FoxO1 and PGC-1α in livers of obese and type 2 diabetic humans

Abstract: Information on insulin resistance in human liver is limited. In mouse diet-induced obesity (DIO), hepatic insulin resistance initially involves: lipid + insulin-induced activation of atypical protein kinase C (aPKC); elevated Akt activity/activation but selective impairment of compartmentalized Akt-dependent FoxO1 phosphorylation; and increases in gluconeogenic and lipogenic enzymes. In advanced stages, e.g., in hepatocytes of type 2 diabetes (T2D) humans, insulin activation of insulin receptor substrate-1(IRS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 49 publications
1
35
0
Order By: Relevance
“…Sajan et al reported that hepatic IRS1 levels diminished as BMI increased [50]. They concluded that hepatic insulin resistance progressed with BMI due to decreases in hepatic IRS1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Sajan et al reported that hepatic IRS1 levels diminished as BMI increased [50]. They concluded that hepatic insulin resistance progressed with BMI due to decreases in hepatic IRS1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only two other studies related to human insulin resistance and obesity were targeting hepatic ceramides. The study by Sajan et al [41] was performed on cryopreserved liver samples from liver transplant donors with varying degree of obesity and diabetic status. Both short-chain and long-chain ceramide species accumulated in livers of obese and T2D subjects with C14:0-Cer and C16:0-Cer positively correlating with BMI values.…”
Section: Discussionmentioning
confidence: 99%
“…Hence our analysis provides insights on possible mechanisms by which differential insulin resistance could be responsible for diabetes, obesity and cancer, simultaneously. Furthermore, our model predicts signalling abnormalities like progressive decrease in IRS and AKT activity along with increase in aPKC and mTOR activity with increase in body mass index (BMI) in human subjects (lean, obese & T2DM) and mouse, with diet induced obesity 59 . These observations can easily be explained by our model where increase in FA and AA levels (in obese and T2DM) lead to respective increase in PKC, mTOR-S6K1p and subsequent inhibition of IRS and downstream kinases like AKTp.…”
Section: Importance Of Feedback Loops and Its Perturbation In Diseasementioning
confidence: 99%